PENERAPAN FILSAFAT OLEH GURU SEKOLAH DASAR - Sakinah, Fitri; Andrea, Jordi; Desyandri, Desyandri; Jamaris, Jamaris (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Educational philosophy is the theoretical basis that underlies approaches, methods, and values ​​in the learning process in elementary school. This research discusses the application of educational philosophy by teachers in elementary schools (SD) with a focus on various philosophical schools that influence educational practice. This research method uses a literature review with descriptive analysis methods. Data was collected through library and documentation techniques by accessing various sources, such as books, journals, and related documents. Data analysis was carried out using a content analysis model. The results and discussion identify the role of teachers as educators, instructors, mentors, leaders, learning managers, and models/exemplars. Several philosophical schools such as Idealism, Naturalism, Pragmatism, Existentialism, and Perennialism, influence educational approaches, methods, and goals. Challenges in implementing educational philosophy for teachers involve limitations in the school curriculum, limited resources, and educators' lack of understanding of the concepts and principles of educational philosophy. This research contributes to understanding how educational philosophy can be integrated into educational practice at the elementary school level. The identified challenges can also become a basis for policymakers and educational decision-makers to increase the application of educational philosophy in the elementary school context, by paying attention to the balance between academic aspects and philosophical values.